1996
DOI: 10.1038/bjc.1996.573
|View full text |Cite
|
Sign up to set email alerts
|

High risk of lymphomas in children of Asian origin: ethnicity or confounding by socioeconomic status?

Abstract: Summary To examine the role of ethnic origin as a risk factor for paediatric lymphoma, a cancer registrybased analysis was undertaken in Yorkshire, UK. Children of Asian ethnic origin were found to have an odds ratio for lymphomas of 1.60 (CI 0.98-2.62), after adjusting for age and sex. After adjusting also for 'super profile group' as an indicator of socioeconomic status, the estimate became 1.99

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…It confirms previous reports, based on smaller regional data sets over longer periods, of an overall Asian excess (Powell et al, 1994) and of a higher proportion of male cases among Asians compared to non-Asians (Varghese et al, 1996). The pattern of type-specific occurrence in these data is also in keeping with previous studies, with higher south Asians rates reported for lymphoma (Powell et al, 1994;Varghese et al, 1996) and retinoblastoma . This might be expected, as there is some overlap in the cases included in these studies, but approximately two-thirds of the cases in this series have not been previously reported and represent a larger population base.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…It confirms previous reports, based on smaller regional data sets over longer periods, of an overall Asian excess (Powell et al, 1994) and of a higher proportion of male cases among Asians compared to non-Asians (Varghese et al, 1996). The pattern of type-specific occurrence in these data is also in keeping with previous studies, with higher south Asians rates reported for lymphoma (Powell et al, 1994;Varghese et al, 1996) and retinoblastoma . This might be expected, as there is some overlap in the cases included in these studies, but approximately two-thirds of the cases in this series have not been previously reported and represent a larger population base.…”
supporting
confidence: 82%
“…Despite substantial religious and cultural heterogeneity within the group as a whole (referred to as south Asian in this paper), differences from other ethnic groups have been demonstrated for a wide range of health outcomes (Soni Raleigh et al, 1990;Wild and McKeigue, 1997;Mather et al, 1998). Previous studies on childhood cancer in the south Asian population have either been limited to regional geographical areas (Muir et al, 1992(Muir et al, , 1995Powell et al, 1994Powell et al, , 1995Varghese et al, 1996) or have not reported incidence or mortality rates (Stiller et al, 1991;Swerdlow et al, 1995) through lack of population denominator data. This study combined numerator data from 4 regional cancer registries with denominator data from the 1991 census, incorporating approximately 80% of the resident south Asian population, to derive the first near national sex-specific estimates of childhood cancer incidence in the south Asian population of England.…”
mentioning
confidence: 95%
“…However, lymphoma rates have been in- Bold type: 95% CI does not include 1.00. creased among South Asian migrants to England, including their English-born children and some Jewish groups moving to Israel. 6,[27][28][29] Although the etiology of non-Hodgkin's lymphoma is unknown, it is likely to involve an aberrant immune response that has been linked to population mixing and undefined infections. 30 -33 Thus second-generation descendents of low-risk areas somehow do not appear to adjust to the high-risk environment of Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…The data on adult immigrants to Sweden are consistent with such data . The data on childhood cancer are limited but those suggest for the offspring of south Asian immigrants in the UK suggest that differences from the native population exist for some neoplasms (Varghese et al, 1996;Cummins et al, 2001). Similarly, the relatively young second-generation Israelis seem to maintain some of the cancer rates from the countries of their parental origin Parkin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Migrant studies have indicated the importance of environment in cancer aetiology (Parkin and Khlat, 1996) with, however, almost exclusive focus on adult cancers of, primarily, the first generation immigrants (Haenszel and Kurihara, 1968;McMichael et al, 1980;Steinitz et al, 1989;Parkin et al, 1990;Balzi et al, 1993;Iscovich and Parkin, 1997;Parkin et al, 1997;McCredie et al, 1999a,b). Exceptions include childhood cancer studies among the offspring of south Asian immigrants to England (Varghese et al, 1996;Cummins et al, 2001).…”
mentioning
confidence: 99%